Effect of friction time on the mechanical properties of AA 6061-T6 continuous drive friction welded joints - Suwanda, Totok; Syaifudin, Eko; Nugroho, Aris Widyo; Ardiyansyah, Nur (Politeknik Negeri Lhokseumawe, 2024)
Continuous drive friction welding (CDFW) is a solid-state method used to join solid cylindrical metals. This process involves several key parameters that influence the strength of the connection, including friction time, friction pressure, and machine speed. The aim of this research was to determine the effect of different friction times on the mechanical properties of Aluminium 6061 CDFW joints. Friction time variations of 2, 3, 4, 5, 6, 7, 8, 9, and 10 seconds were used in the welding process, while other parameters remained constant: friction pressure at 30 MPa, upset pressure at 70 MPa, upset time at 2 seconds, and engine speed at 1000 rpm. Microstructure observations, Vickers microhardness testing, and tensile testing were conducted to assess the impact of friction time on the joint results. Analysis of the microstructure revealed changes, such as recrystallization, in the joint area. It was observed that the grain size in the joint area was smaller compared to that of the heat-affected zone (HAZ) and the parent metal. Hardness testing showed a decrease in hardness value with increasing distance from the joint. In the tensile test, the highest tensile strength of 215.76 MPa was achieved with a friction time of 6 seconds, while the lowest tensile strength of 78.60 MPa was obtained with a friction time of 2 seconds